Tadkhīl al-Tarbiyah al-Islāmiyyah fī Nuṣūṣ al-Qirāʾah li-Taʿlīm al-Lughah al-ʿArabiyyah - Lahmuddin Lahmuddin (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Reading is the key to every aspect of individual and social life. It serves as the foundation of knowledge and learning, the primary means of acquiring information, and an essential tool for intellectual and cultural development. Moreover, reading is one of the most effective means of integrating Islamic education into the minds and hearts of learners. One of the most important methods of teaching reading is to begin each lesson with a reading text. A text is more than merely a discourse or a collection of statements; rather, it redistributes the linguistic system by revealing the relationships among communicative words and expressions while referring to both explicit information and various patterns of preceding and contemporaneous discourse. Therefore, selecting appropriate reading texts is a crucial aspect of instructional design in reading education. In addition to developing reading proficiency, these texts should also serve the purpose of integrating Islamic educational values into students and readers. Among the most effective educational texts for teaching reading are inspiring stories, such as narratives about the Prophet's Companions and Muslim scholars, which convey valuable moral lessons rooted in Islamic education. Furthermore, carefully selected passages from the Qur'an and authentic Prophetic traditions (Hadith), including verses concerning the rights of parents and hadiths on proper social conduct, provide rich educational content. Literary texts—such as poetry, prose, sermons, counsels, maxims, and proverbs—also play an important role in Arabic language instruction. These literary works embody profound Islamic educational values and leave a lasting impact on students, particularly in the teaching of Arabic reading skills.